PERBEDAAN PERENDAMAN PLAT RESIN AKRILIK PADA TABLET PEMBERSIH GIGI TIRUAN EFFERVESCENT DAN AIR REBUSAN DAUN SIRIH TERHADAP PENURUNAN JUMLAH KOLONI JAMUR CANDIDA ALBICANS - Roza Restu Pambudi; Ratna Sulistyorini; Lisa Oktaviana Mayasari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background: Denture  plaque  is  an  important  factor that  can  caus e palatal mucos a inflammation and denture s tomatitis . Acrylic res in denture and oral cavity hygiene can be maintained from Candida albicans contamination  by  immers ing  denture  in  denture  cleans er at  night.  Denture cleans er can  be  made  from chemical  material,  s uch  as  denture  cleans er  tablet  effervescent and traditional  material  s uch  as  betel leafboiled  water. Objective  : The aim of this  s tudy is to inves tigate the difference between acrylic res in plate immers ion in denture cleaner tablet effervescent and betel leaf boiled water concerning   the    decreas e ofCandidaalbican samount. Methodes  : This is an experimental laboratory  res earch. 24 acrylic res in plates  are divided into 3 groups : group  1, acrylic  res in  immers ed  in  aquades  for 6 hours , group  2, acrylic res in is immers ed in betel leaf boiled water for 6 hours , and grou p 3, acrylicres in is immers ed in denture cleans er tableteffervescent in 15 minutes. Result:  Statis tical  analys is  with  ANOVA  tes t  which  is  then  continued with  post -hoc  test s hows  the s ignificant  difference  between  betel leaf boiled  water and  denture cleans er tablet  effervescent  (p<0.05). Conclus ion : It can be concluded  from this s tudy that there is a lot betel leaf boiled water concerning the decrease of Candida albicans fungal colony of the denturecleanser tablet effervescent. Keywords: Candida albicans, betel leaf boiled water, denture cleanser tablet effervescent.